High-Throughput Sequencing Technology Assisted Investigation of the Correlation Between Intestinal Flora, Serum Biochemistry, Blood Lipids, and Tumour Markers in Patients with Gastric Cancer and Healthy Plateau Residents - Zhu, Linghong; Wang, Bo; Liu, Linxun; Han, Pei; Ji, Li; Zhang, Zilong; Zhang, Jingni (Combinatorial Chemistry & High Throughput Screening, 2024)
Aim: The goal is to use high-throughput sequencing technology to compare and study the structure and variety of intestinal flora in people with gastric cancer and healthy people in the Qinghai-Tibet Plateau. Background: Recent research has connected gut flora structure to numerous disorders. Metabolites, endotoxins, and immunomodulatory modulation might cause gastrointestinal or other systemic diseases and affect gastric cancer treatment and prognosis. We used the correlation study to uncover biomarkers associated with good intestinal flora and gastric cancer groups on the plateau to investigate their involvement in gastric cancer development. Objectives: To investigate the possible links between intestinal flora and gastric cancer in the Qinghai Plateau region using a variety of clinical phenotypic data and to investigate the flora that may be linked to gastric cancer. Methods: The 22 Qinghai Province tertiary hospital gastric cancer patients and 30 healthy people had their fresh faeces collected. To examine intestinal flora diversity and composition, 52 patients underwent 16S rDNA high-throughput gene sequencing of intestinal bacteria. The correlation between clinical phenotypes and the top 15 dominant intestinal flora at the phylum level was analyzed. Results: The difference in total protein TP between the healthy group and the gastric cancer group was statistically significant (P<0.001). Globulin was significantly different (P<0.05), TC of total cholesterol was significantly different (P<0.05). High-density lipoprotein showed statistical significance (P<0.05).The difference in low-density lipoprotein was statistically significant (P<0.001). Alphafetoprotein was significantly different (P<0.05). CA72-4 carbohydrate antigen (P<0.05). Conclusion: There were significant differences in total protein, globulin, total cholesterol, high density lipoprotein, low-density lipoprotein, alpha-fetoprotein and carbohydrate antigen CA72-4 in patients with gastric cancer in the plateau area compared with the healthy group, and the different clinical variables were correlated with intestinal flora at some phylum and genus levels.
Keywords: genus levels